Profil Fitokimia dan Aktivitas Antioksidan Ekstrak Kayu Manis (Cinnamomum burmanii Blume) Asal Jambi dan Lampung Menggunakan Py-GCMS: Phytochemical Profile and Antioxidant Activity of Cinnamon (Cinnamomum burmanii Blume) Extract from Jambi and Lampung Using Py-GC/MS - Liana Verdini; Tiara Kurnia Khoerunnisa; Nurbani Kalsum; Upy Raudotul Jannah (Universitas Djuanda, 2026)
Cinnamon is a spice rich in phenolic compounds and flavonoids with significant biological activities. This study aims to analyze the phytochemical profile and antioxidant activity of cinnamon (Cinnamomum burmanii Blume) extracts from Jambi and Lampung. Extraction was performed using an ultrasonic-assisted method (40 kHz, 66 minutes, 35°C). Qualitative identification was conducted via Pyrolysis Gas Chromatography-Mass Spectrometry (Py-GCMS), while quantitative analysis focused on total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity (DPPH). Results showed that geographical origin and solvent type significantly influenced the chemical profile. Py-GCMS identified key compounds such as 2-phenyl-5-carboxy-2H-1,2,3,4-tetrazole in Lampung extract and 1-phenyl-4-carboxy-4,5 in Jambi extract. Based on the high concentration of bioactive components in the initial screening, Jambi aquadest extract was identified as the best treatment. Quantitative analysis of this extract yielded a TPC of 64.51 mg/g GAE, TFC of 14.27 mg/g QE, and antioxidant activity of 15.74%. These findings confirm a strong correlation between phenolic content and antioxidant capacity in cinnamon extracts.